Corrosion inhibition of mild steel by 2-(2-methoxybenzylidene) hydrazine-1-carbothioamide in hydrochloric acid solution: Experimental measurements and quantum chemical calculations - Ferkous, Hana; Djellali, Souad; Sahraoui, Rachid; Benguerba, Yacine; Behloul, Hamza; Cukurovali, Alaaddin (Elsevier, 2020)
Corrosion inhibition effect of 2-(2-methoxybenzylidene) hydrazine-1-carbothioamide (MBHCA) for mild steel in acidic medium (HCl/1 M) is evaluated using polarization tests (potentiodynamic), electrochemical impedance spectroscopy (EIS) and gravimetric method. The parameters of adsorption of the inhibitor on the metal surface are determined and the external morphology of the metal is examined by SEM. The results show that the rate of steel corrosion is significantly reduced with augmentation in the Schiff base concentration where the inhibition efficiency of MBHCA reaches a maximum value of 97.8% at 200 ppm. Polarization measurements reveal that the presence of MBHCA declines considerably the current and shifts the corrosion potential to higher values indicating that this Schiff base acts as a mixed type inhibitor with a cathodic dominance. From the thermodynamic results, the inhibitor adsorption on the steel surface via the chemisorption mechanism is confirmed and Langmuir model is the most suitable to describe the MBHCA adsorption. Moreover, the metal surface examination with SEM confirms the efficiency of MBHCA to keep mild steel protected against the used aggressive medium. Correlation of quantum chemical calculations with experimental results of the present work is discussed according to the Density Functional Theory method (DFT) and molecular dynamics simulation (MD). (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Schiff base; Corrosion inhibitor; Impedance spectroscopy; Polarization; Adsorption; DFT; COSMO-RS